Penentuan Arah Pergerakan Lindi Dengan Metode Geolistrik Pada Tempat Pembuangan Akhir (TPA) Sampah Daerah Maiwa, Kecamatan Maiwa, Kabupaten Enrekang, Sulawesi Selatan - Fauzi Arifin; Haerany Sirajudin; Hasbi Bakri (Universitas Muslim Indonesia, 2022)
One of the important aspects in urban solid waste management is the problem of leachate which if it is not managed properly will cause a serious threat to the environment, because leachate production will enter underground water streams and also surface water. Leachate is a liquid that flows or 'dissolves' from landfills, with a composition that varies depending on the age of the landfill and the type of waste contained in it. This leachate usually contains dissolved bacteria or and insoluble bacteria. The study site is composed of clastic sedimentary rocks in the form of sandstones and conglomerates, which are included in the Miocene Pliocene Sand (Tmps) tertiary rock formations and the Miocene Conglomerate Tertiary (Tmc). The results of previous studies found that the area where the waste landfill is located on coarse to fine-grained rocks, which is very likely that the flow of leachate contained in the waste landfill location will affect the quality of the water system around the waste landfill location. From the results of this study, it can be known the direction of leachate flow by the geoelectric method and the extent of its effect on the groundwater system in the area around the landfill